Evaluation of glyphosate and 2,4-Dichlorophenoxyacetic acid combinations to control glyphosate-resistant hairy fleabane [(Conyza bonariensis (L.) Cronquist] - Vorster, Barend Juan (University of Pretoria, 2022)
Dissertation (MSc Agric (Agronomy))--University of Pretoria 2022.